Strategies to empower adolescent women and prevent gender violence - Charry Aysanoa, Juan Marciano (2021)
Objective: it was to promote the implementation of a set of empowerment strategies for adolescent women to prevent gender violence. Method: corresponds to the interpretive paradigm, inductive method, qualitative approach and phenomenological design and descriptive level; The sample consisted of nine women, inhabitants of the Centro Poblado Menor de Carmen Alto in the district of Nuevo Imperial, province of Cañete, department of Lima, to whom a semi-structured in-depth interview was applied. Results: the existence of a marked inequality of powers, roles and traditional conceptions of gender and a great risk of being a woman is reported, a condition that if not addressed will last for a long time and with the loss of all rights to a safe life and free from violence, so the implementation of empowerment strategies for adolescent women is an imperative and starts from raising awareness, addressing self-knowledge and the ability to make decisions to contribute significantly to the prevention of gender violence. Conclusions: the nine adolescents participating in the study have been empowered with strategies related to the development of knowledge regarding their rights, interests, conditions; coping skills that have made it possible to strengthen their way of thinking and acting in the face of acts of gender violence; for which the appropriate relationship with their families, with the school and with the community has been conveniently established, and that, at the same time, these constitute support instruments for the consolidation of female empowerment in the face of male hegemony that, unfortunately, persists even in this part of the country. It is feasible to work on a new social construction of being a man and a woman, promoting the active participation of adolescent girls.